Introduction: Ethnographie, performance et imagination - Kazubowski-Houston, Magdalena; Magnat, Virginie (Anthropologica, 2018)
This introduction to the thematic section entitled “Ethnography, Performance and Imagination” explores performance as “imaginative ethnography” (Elliott and Culhane 2017), a transdisciplinary, collaborative, embodied, critical and engaged research practice that draws from anthropology and the creative arts. In particular, it focuses on the performativity of performance (an event intentionally staged for an audience) employed as both an ethnographic process (fieldwork) and a mode of ethnographic representation. It asks: can performance help us research and better understand imaginative lifeworlds as they unfold in the present moment? Can performance potentially assist us in re-envisioning what an anthropology of imagination might look like? It also inquires whether working at the intersections of anthropology, ethnography, performance and imagination could transform how we attend to ethnographic processes and products, questions of reflexivity and representation, ethnographer-participant relations and ethnographic audiences. It considers how performance employed as ethnography might help us reconceptualise public engagement and ethnographic activism, collaborative/participatory ethnography and interdisciplinary research within and beyond the academy. Finally, this introduction provides a brief overview of the contributions to this thematic section, which address these questions from a variety of theoretical, methodological and topical standpoints.